2009
DOI: 10.1038/sj.bjc.6605259
|View full text |Cite
|
Sign up to set email alerts
|

Surgery with curative-intent in patients treated with first-line chemotherapy plus bevacizumab for metastatic colorectal cancer First BEAT and the randomised phase-III NO16966 trial

Abstract: BACKGROUND: Complete resection of metastases can result in cure for selected patients with metastatic colorectal cancer. METHODS: First BEAT evaluated the safety of bevacizumab with first-line chemotherapy in 1914 patients. Prospectively collected data from 225 patients who underwent curative-intent surgery were analysed, including an exploratory comparison of resection rate in patients treated with different regimens. NO16966 compared efficacy of oxaliplatin-based chemotherapy plus bevacizumab or placebo in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(90 citation statements)
references
References 28 publications
(17 reference statements)
7
80
0
3
Order By: Relevance
“…22,39 Furthermore, in the subpopulation with liver-only metastatic disease in the BEAT and the First BEAT studies, 15.2% of patients underwent curative-intent hepatic metastasectomy. 26,39 Other studies too found only 14% of patients 40 or none 35 eligible for surgery with a curative intent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,39 Furthermore, in the subpopulation with liver-only metastatic disease in the BEAT and the First BEAT studies, 15.2% of patients underwent curative-intent hepatic metastasectomy. 26,39 Other studies too found only 14% of patients 40 or none 35 eligible for surgery with a curative intent.…”
Section: Discussionmentioning
confidence: 99%
“…22,39 Furthermore, in the subpopulation with liver-only metastatic disease in the BEAT and the First BEAT studies, 15.2% of patients underwent curative-intent hepatic metastasectomy. 26,39 Other studies too found only 14% of patients 40 or none 35 eligible for surgery with a curative intent. Although differences in study design, patient selection and study regimens between studies would preclude a direct comparison, a much higher resection rate (42.2%) was observed in the present study: the resection rate observed in the present study was higher than that with the regimen XELIRI (a combination of capecitabine and irinotecan) and FOLFIRI (resection rate: 24%) 41 and regimen FOLFOX and FOLFIRI (resection rate: 35%), 31 and consistent with a previous report that demonstrated 40% conversion rate following neoadjuvant chemotherapy with oxaliplatin, bevacizumab and capecitabine.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases only radical surgery offers the chance of long-term survival. The safety and efficacy of bevacizumab in preoperative setting were evaluated in a post hoc analysis of the NO16966 and First BEAT clinical trials [45]. In the group of patients with metastases limited to the liver, 12.3% of patients treated with chemotherapy plus bevacizumab (26 of 211) eventually received a R0 resection, compared with 11.6% of patients (24 of 207) treated with chemotherapy plus placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Disease‐specific mortality of progressive CRC has decreased significantly in past decades with novel chemotherapeutic agents, such as oxaliplatin and irinotecan, and molecular targeted drugs, such as bevacizumab, a recombinant humanized monoclonal antibody that targets vascular endothelial growth factor (VEGF) 3. Adding bevacizumab to chemotherapy significantly reduces the residual viable tumor cell volume in resected tumors and increases the proportion of patients eligible for liver metastasis resection, when compared with chemotherapy alone 4, 5…”
Section: Introductionmentioning
confidence: 99%